Üç İstanbul Romanı Üzerine Sosyolojik Okuma Denemesi - Alver, Köksal (Kitabevi, 2003)
This paper invested Mithat Cemal's Üç İstanbul, novel that took three consequtive outstanding period of Turkish politic history as its themes. In the novel ruling time of Abdulhamid II, Party of Union and Progress and İstanbul during the occupation years were told; power, degeneration, political movements, political tricks were dealt with by Adnan's metamorphosis. All these are tried to be done by means of a sociologic reading, so social understanding is treated in order to analyze the novel and its content.
A Sociologic Reading Attempt on Üç İstanbul
Keywords: Üç İstanbul; Mithat Cemal; Turkish Novel; Abdulhamid II; Party of Union and Progress